Linking Elk movement and resource selection to hunting pressure in a heterogeneous landscape - Shawn M. Cleveland; Mark Hebblewhite; Mike Thompson; Robert Henderson (Wildlife Society Bulletin)
Abstract Elk (Cervus elaphus) are increasing in fragmented landscapes that result from exurban human development throughout western North America, which increases human–wildlife conflicts and poses a challenge to wildlife managers. Elk hunting must often be intensively managed to reduce population growth rate, crop depredation, and habituation to humans. However, little was known about the indirect effect hunting has on anti‐predator behavior, movement, resource selection, and human–elk conflicts. We outfitted elk with global positioning system (GPS) collars in the wildland–urban interface (WUI) of Missoula, Montana, USA, 2007–2009, to test the indirect effects of hunting on elk. We used data from 9 GPS‐collared adult female elk during 3 hunting seasons with increasing hunting pressure (2007–2009) to test relationships between movement rates measured by first passage time (FPT) and resource selection. Elk movement rates were lower approximately 750 m from houses and trails, resulting in resource selection for areas approximately 1,200 m from houses and trails; this suggested that habituation to humans contributed to human–wildlife conflict. Movement rates increased with increasing hunting pressure, and were lower in general versus focal hunting seasons and with archery versus rifle hunting. Thus, intensive hunting seasons in the WUI increased elk movement rates and exposure to hunter predation risk, as predicted. These results support the hypothesis that elk modify their behavior in relation to temporal and spatial variation in human predation risk. In the intensively managed WUI, our results demonstrate that even small increases in the area hunted and increases in intensity can indirectly change resource selection and movement rates of elk, potentially reversing recent trends of increasing habituation in WUI elk populations. © 2012 The Wildlife Society.